Effect of rumen protected amino acid supplementation on performance of Holstein cows fed rations containing high levels of canola meal - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.